Global Genomic Characterization of Salmonella enterica Serovar Telelkebir - Qiu, Yu-feng; Nambiar, Reshma B.; Xu, Xue-bin; Weng, Shun-tai; Pan, Hang; Zheng, Kui-cheng; Yue, Min (Frontiers in Microbiology, 2021)
Nontyphoidal Salmonella (NTS) is a common cause for self-limiting gastroenteritis, representing a public health concern globally. NTS is one of the leading causes of foodborne illnesses in China; however, the invasive infection caused by NTS is largely underappreciated. Here, we reported an NTS invasive infection caused by an infrequently reported serovar Telelkebir (13,23:d:e,n,z15) strain FJ001 in China, which carries antimicrobial-resistant genes (fosA7 and aac(6′)-Iaa) and typhoid-toxin genes (cdtB, pltA and pltB). By conducting the whole genomic sequencing, we also investigated the relatedness of this strain with an additional 120 global contextual Salmonella enterica serovar Telelkebir (S. Telelkebir) isolates, and assessed the antimicrobial-resistant determinants and key virulence factors using the available genomic dataset. Notably, all 121 (100%) of the S. Telelkebir strains possessed the typhoid toxin genes cdtB, pltA and pltB, and 58.67% (71/121) of S. Telelkebir harbored antimicrobial-resistant gene fosaA7. The study by core genome multilocus sequence typing (cgMLST) and core single nucleotide polymorphism (SNP) based phylogenomic analysis demonstrated that the S. Telelkebir isolates from different sources and locations clustered together. This suggests that regular international travels might increase the likelihood of rapid and extensive transmissions of potentially pathogenic bacteria. For the first time, our study revealed the antimicrobial resistance, virulence patterns, and genetic diversity of the serovar S. Telelkebir isolate in humans and similar isolates over the world. The present study also suggests that genomic investigation can facilitate surveillance and could offer added knowledge of a previously unknown threat with the unique combination of virulent and antimicrobial-resistant determinants.